The Intestinal Transporter SLC30A1 Plays a Critical Role in Regulating Systemic Zinc Homeostasis - Shumin Sun; Enjun Xie; Shan Xu; Suyu Ji; Shufen Wang; Jie Shen; Rong Wang; Xinyi Shen; Yunxing Su; Zijun Song; Xiaotian Wu; Jiahui Zhou; et al. (Advanced Science)
Abstract The essential trace element, zinc, regulates virtually all aspects of cellular physiology, particularly cell proliferation and survival. Diverse families of metal transporters, metallothioneins, and metal‐responsive transcriptional regulators are linked to zinc homeostasis. However, the mechanism underlying the regulation of systemic zinc homeostasis remains largely unknown. Here, it is reported that the intestinal transporter SLC30A1 plays an essential role in maintaining systemic zinc homeostasis. Using several lines of tissue‐specific knockout mice, it is found that intestinal Slc30a1 plays a critical role in survival. Furthermore, lineage tracing reveals that Slc30a1 is localized to the basolateral membrane of intestinal epithelial cells (IECs). It is also found that Slc30a1 safeguards both intestinal barrier integrity and systemic zinc homeostasis. Finally, an integrative analysis of the cryo‐EM structure and site‐specific mutagenesis of human SLC30A1 are performed and a zinc transport mechanism of SLC30A1 unique within the SLC30A family, with His43 serving as a critical residue for zinc selectivity, is identified.